Clinical-epidemiological behaviour of patients after cataract surgery - Leydi E. Jacomino Hernández; Idalia Triana Casado; Juan C. Medina Perdomo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: Cataract is the leading cause of blindness in the world. Its only effective treatment is surgery, with a high rate of efficiency, but it is not always practiced due to several reasons that limit access to health services. Objective: To identify clinical and epidemiological behaviour of patients after cataract surgery. Methods: An observational, descriptive and cross-sectional study conducted in the "José Joaquín Palma" Ophthalmology Center in the town of San Cristóbal, Guatemala. We included all patients over 18 years old meeting the inclusion criteria who had had a cataract surgery between July and December 2007. The following variables were analyzed: age, sex, skin color, place of origin, ocular and systemic personal medical history, etiologic type of cataract and intra and immediate postoperative complications. Results: 63.3% of the patients are in the 60 years on age group, with a slight predominance of females (51.89%) and most of them come from the rural areas (66.66%). Among personal medical histories myopia was detected (14.17%) and among systemic medical histories there were arterial hypertension (25.98%) and diabetes mellitus (22.04%). Senile cataract was more frequent (52.75%). The most frequent intraoperative complications were posterior capsule ruptures with or without vitreous loss (29.548% and 3.37% respectively) and corneal edema in the immediate postoperative (5.48%). Conclusions: The results of clinical and epidemiological characterization of patients after cataract surgery included in this series do not differ from those of similar studies, except for the personal glaucoma history.